Family and friends’ expected support to parents of children with disabilities - Vučinić, Vesna; Martać, Valentina; Anđelković, Marija (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Informal and formal support to parents of children with disabilities affects family functioning and life satisfaction of family members in many ways. Objective. The aim of this research was to determine the extent to which parents of children with disabilities expected support of their family and friends. Methods. The sample included 65 parents of children with disabilities, most of whom were mothers (N = 62, P = 95.4%). The Social Support Behaviors – SS-B scale (Vaux et al., 1987) was used to examine the expected support of family and friends. Results. Descriptive statistics showed that parents counted on family members’ support much more than on their friends’ support. Parents of children with multiple disabilities, unemployed parents, and those who lived in rural areas had lower expectations regarding family and friends’ support compared to other groups. Their expectations were the lowest in the segments of financial and physical support. Conclusion. Extended family members were expected to provide greater help in all five support dimensions (emotional, social, physical, financial, and counselling). The analysis of individual items within these dimensions indicates the existence of various expectation levels within the same dimension, which is the result of specific requirements.